PENDEKATAN PSIKOLOGI ANAK DALAM PROSES PEMBELAJARAN AKTIF - Nor Mubin (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
The child's psyche and personality are very important for self-understanding and give understanding to others outside of us, because the impressions of childhood are very influential on the formation of our attitude and outlook on life, whether projected in the present or in the future. Even if the attitude of trying his best to forget it in adulthood and old age, but the child's world still puts a strong stamp on his personality. In modern society, the position and approach of psychology can be said to be an effective means for the success of the goals of the learning to which it aspires, both individually and as a social group. The active learning strategy is a teaching and learning strategy that aims to improve the quality of education, and to achieve student involvement effectively and efficiently in the need for integrated, balanced, and sustainable engagement learning between media, methods, teachers and students. Among these methods are directing to the optimal type of learning interaction, demanding various types of student activities, teaching and learning resources that are in accordance with the goals to be achieved, using multi methods, using multi-media that vary, directing to multi-learning resources, Active learning strategies have a positive impact including students being motivated, the level of student activity in the teaching and learning process